2020
DOI: 10.1097/jom.0000000000001899
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Correlation Between Multiple Chemical Sensitivity and Personality Using the Quick Environmental Exposure Sensitivity Inventory Questionnaire and the Temperament and Character Inventory

Abstract: Objective: We conducted an analysis using the Quick Environmental Exposure Sensitivity Inventory to examine the correlation between multiple chemical sensitivity (MCS) and personality traits by using temperament and character inventory, and environmental exposures. Methods: An anonymous questionnaire was distributed to 667 employees working at an IT manufacturing plant in Japan. Variables including chemically sensitive population (CSP), personality, and environmental ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…Numerous studies have reported a higher prevalence rate of MCS and chemical intolerance in women than in men [ 3 , 5 8 , 31 33 ], consistent with our findings. Similarly, several studies have reported a higher prevalence of EHS in women than men [ 16 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Numerous studies have reported a higher prevalence rate of MCS and chemical intolerance in women than in men [ 3 , 5 8 , 31 33 ], consistent with our findings. Similarly, several studies have reported a higher prevalence of EHS in women than men [ 16 ].…”
Section: Discussionsupporting
confidence: 92%
“…However, several characteristics of MCS remain unclear, including the mechanism underlying its onset, risk factors for onset and aggravation, its relationship with allergic diseases, and psychosomatic and mental disorders. During the last decade, the prevalence of self-reported MCS has been reported to be 3–26%, and it is higher in women than in men [ 3 8 ]. Additionally, there are age-related differences in the prevalence of MCS, with adults showing a higher prevalence than older adults and youth [ 9 ].…”
Section: Introductionmentioning
confidence: 99%